PRINSIP KEHATI-HATIAN DALAM MENETAPKAN TERSANGKA SEBAGAI PARAMETER PENGUJIAN TINDAKAN PENYIDIK MELALUI PRAPERADILAN - Rocky Marbun; Debby Monica Sinaga (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Investigators, both in the Indonesian National Police Institution and who are in other law enforcement institutions, in the investigation process have the authority to determine someone suspected of committing a criminal offense as a suspect, as regulated in Article 7 paragraph (1) of the Criminal Procedure Code. However, in the level of criminal justice practices, investigators interpret the authority absolutely by establishing someone as a suspect based on a minimum of two pieces of evidence. Although, the Constitutional Court has given limits to the determination of suspects, however, with the issuance of the Supreme Court Regulation Number 4 of 2016 concerning the Prohibition of Review of Pre-Trial Decisions (SCR No. 4/2016) gives limits to the establishment of formal requirements. Based on this, researchers submit the problem “What is the form of violation of the precautionary principle in establishing a person as a suspect who is the object of a pretrial application?” This study uses a normative juridical method using secondary data through literature studies. The results of this study indicate an obligation for investigators to meet the investigation standards in the process of determining the suspect based on the decision of the Constitutional Court Number 21/PUU-XII/2014, the Criminal Procedure Code, and the Internal Regulations of each Law Enforcement Institution.Keywords: Determination of Suspect, Precautionary Principle, Pretrial, Evidence, Investigator